AR-Assisted Children Book For Smart Teaching And Learning Of Turkish Alphabets - Ahmed L. Alyousify; Ramadhan J. Mstafa (Virtual Reality & Intelligent Hardware, 2022)
Augmented reality (AR), virtual reality (VR), and remote-controlled devices are driving the need for a better 5G infrastructure to support faster data transmission. This paper emphasizes that mobile AR is a viable and widespread solution that can easily scale to millions of end-users and educators since it is lightweight, low-cost, and cross-platform. Low-efficiency smart devices and lengthy latency for real-time interactions via regular mobile networks are major barriers to using AR in education. The good news is that the upcoming 5G cellular networks can mitigate some of these issues via network slicing, device-to-device communication, and mobile edge computing. In this paper, we rely on technology to solve some of these problems. The proposed software monitors Image Targets on a printed book and renders 3D objects and alphabet models. In addition, the application considers phonetics. The sound (Phonetic) and 3D representation of the letter are played as soon as an image target is detected. The Turkish alphabet 3D models were created in Adobe Photoshop using Unity3D and the Vuforia SDK. The proposed application teaches Turkish alphabets and phonetics by using 3D object models, 3D letters, and 3D phrases including those letters and sounds.